The Effects of Shopping Orientations, Consumer Innovativeness, Purchase Experience, and Gender on Intention to Shop for Fashion Products Online - Ratih Puspa Nirmala; Ike Janita Dewi (Gadjah Mada International Journal of Business, 2011)
Nowadays, many fashion retailers or marketers use the power of internet to promote and sell their products. This research examines the effects of consumers’ shopping orientations (brand/fashion consciousness, shopping enjoyment, price consciousness, convenience/time consciousness, shopping confidence, in-home shopping tendency), consumer innovativeness, online purchase experience for fashion products, and gender on consumers’ intention to shop for fashion products online. Data were collected through online surveys from the population of internet users in Indonesia, aged between 15 and 30 years old (generation Y), who had bought or browsed fashion products through the internet (N=210). This research is a quantitative research which uses purposive sampling and multiple regression analysis. Results show that the effects of several shopping orientations (shopping enjoyment, price consciousness, in-home shopping tendency), consumer innovativeness, online purchase experience for fashion products, and gender, are significant on consumers’ intention to shop for fashion products online. Furthermore, gender is marginally significant related to consumers’ intention to shop for fashion products online. Surprisingly, women tend to have lower intentions to shop for fashion products online compared to men.